Substantive Capacity of Management Accounting Information Systems and the Needs of Reporting Sustainable Development – Theoretical and Practical Aspects - Baran, Wioletta; Raulinajtys-Grzybek, Monika; Karwowski, Mariusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: To verify the usefulness of management accounting in reporting on sustainable development. Research Design & Methods: A management accounting information system was described using GMAP standards. The scope of information required for reporting of sustainability development was determined on the basis of GRI. The empirical study used the Delphi method. Findings: The research shows that the highest importance of management accounting was ascribed to reporting on the organisation’s activities, its stakeholders, and the direct economic impact on the environment. Reporting on working conditions and impact on the local community were rated slightly lower, while other areas came in as “fairly significant”, the lowest level of the three. Implications / Recommendations: Management accounting can be useful in reporting on sustainable development, determined on the basis of GRI. Contribution: The article confirms the usefulness of management accounting in reporting on sustainable development. This is important from the point of view of social systems theory, where the topic remains poorly described, as well as in practice, particularly at large global organisations, which are increasingly using modified managerial accounting tools in this area.